The Behaviour of Intelligent Investors at Financial Markets: Insight from Slovenian Investors - Vesna Trančar (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
Intelligent investors differ from speculative or non-professional investors in the fact that intelligent investors act countercyclically; that is, they act against the trend, or otherwise, they buy when prices have already fallen and sell when their rate of selected investment has already risen. An example of countercyclical behavior can also be explained by the thinking of professional investor Warren Buffett, who points out a simple investment rule: "Be scared when others are greedy, and be greedy when others are scared." Since crypto markets have recently emerged, there is a need for researching the best strategy for investments in their financial instruments. To get an insight into the behavior of Slovenian investors, in-depth interviews were conducted with a sample of financial experts. The article presents tips for the correct responses of intelligent investors in financial markets.
Keywords: G41; 330; intelligent investments; intelligent investors; crypto market; financial instruments